2018
DOI: 10.11604/pamj.2018.29.193.13111
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological pattern of primary bone tumours and tumour-like lesions in Ile-Ife, Nigeria

Abstract: IntroductionBone tumours are relatively rare in comparison with neoplasms in other parts of the body. Previous studies have noted higher frequencies of these tumours in young adults with potentially devastating consequences.MethodsThis study aimed to demonstrate the histopathological pattern of primary bone tumours and tumour-like lesions in Ile-Ife, Nigeria with emphasis on relative frequencies and distribution according to age, sex and anatomical location. A 13 year (1991-2003) retrospective study was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria. Among 43 benign tumors, we diagnose majority (25.6%) of cases as osteochondroma followed by 21 % cases of Benign Giant Cell Tumor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria. Among 43 benign tumors, we diagnose majority (25.6%) of cases as osteochondroma followed by 21 % cases of Benign Giant Cell Tumor.…”
Section: Discussionsupporting
confidence: 91%
“…The bone tumors are comparatively rare. 1 The exact frequency of bony neoplasm is still controversial, as many benign lesions are not biopsied and recorded. In general when we exclude the myeloma and lymphoma, the tumors of bone having malignant biological behaviour make up only 0.2% of all malignancies in adults and approximately 5% of all malignancies in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relative frequency of osteosarcoma in African countries was higher (Sudan 5.3% and Uganda 6.4%) when compared to European countries (2%-3%). In a more recent study, Aina et al demonstrated that primary bone tumors accounted for 1.26% of the total malignant neoplasms diagnosed between 1991 and 2003 in Ile-Ife, South West Nigeria (48). This frequency is similar to that reported in Ibadan (1.28%), another province in South West Nigeria (49).…”
Section: Epidemiologymentioning
confidence: 63%
“…Seven hospital-based retrospective studies involving 773 cases of primary bone tumours were included in this systematic review. 1,2,9, [14][15][16][17] The studies were published between 2007 and 2018 involving four of the six geopolitical zones in Nigeria. The characteristics of the studies are shown in Table I…”
Section: Description Of Studiesmentioning
confidence: 99%